2011
DOI: 10.3108/beej.17.5
|View full text |Cite
|
Sign up to set email alerts
|

Using Fremyella diplosiphon as a Model Organism for Genetics-based Laboratory Exercises

Abstract: In this pilot study, a genetics-based laboratory exercise using the cyanobacterium Fremyella diplosiphon was developed and trialled with thirteen Natural Sciences undergraduates. Despite most students only having limited prior exposure to molecular genetics laboratory methods, this cohort confirmed that they were able to follow the protocol and create a range of mutants. Supporting evidence that this was a useful exercise was derived from eight of these students going on to full-time laboratory research to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One visually appealing example was Fremyella. This algae changed color based on the light source, and placing test tubes under different colors of light allowed students to observe varying hues . Over the seven-day lab, students recorded and analyzed data specifically relating to the dissolved oxygen content.…”
Section: Biology Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…One visually appealing example was Fremyella. This algae changed color based on the light source, and placing test tubes under different colors of light allowed students to observe varying hues . Over the seven-day lab, students recorded and analyzed data specifically relating to the dissolved oxygen content.…”
Section: Biology Implementationmentioning
confidence: 99%
“…This algae changed color based on the light source, and placing test tubes under different colors of light allowed students to observe varying hues. 39 Over the seven-day lab, students recorded and analyzed data specifically relating to the dissolved oxygen content. As a second lab portion, to extract the oil from the algae, students used an olive press (yielding about 75% of the oil), however, in the upcoming year's chemistry class, students had the option of using an additional hexane solvent method to remove the algae oil (yielding about 95% of the oil).…”
Section: Photosynthetic Rate Of Algae Under Varying Conditionsmentioning
confidence: 99%
“…Fremyella diplosiphon is a well-studied cyanobacterial species that has great potential as a third-generation biofuel agent due to its fatty acid methyl esters . In addition to growth in varying light intensities by modifications of its light-harvesting complexes, the organism is extremely amenable to genetic transformation . Efforts to enhance value-added traits such as halotolerance and cellular lipid content in this species have enabled unique environmental applications. , A report by Vass et al has indicated that the Phr A gene plays a role in the DNA repair mechanism of Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%